DEVELOPMENT OF CLASSPOINT-BASED LEARNING MEDIA ON CREATIVE ECONOMY FOR GRADE 6 AT UPT SPF SDN PERCONTOHAN PAM MAKASSAR (PIONIR: JURNAL PENDIDIKAN, 2025)
The lack of engaging and interactive learning media in elementary school social science education has contributed to students' low interest and achievement, especially in understanding creative economy concepts. This study aims to develop ClassPoint-based learning media on creative economic materials. measure the validity of ClassPoint-based learning media on creative economic materials and determine the effectiveness of ClassPoint-based learning media on student learning outcomes. The method used in this research is research and development (R&D) with Robert Maribe Branch's 2009 development model, namely analysis, design, development, implementation, and evaluation (ADDIE). The subjects used in this study were grade VI Saoraja students with a total of 20 students. Data collection techniques and instruments in this study through observation, interviews, learning material validation sheets, learning media validation sheets, teacher response questionnaires, and student response questionnaires. Then the data analysis technique by giving scores to the validation results and response questionnaires, calculating the percentage score of the validity results and response questionnaires, calculating the average percentage score of the validity results and response questionnaires, and categorizing the average percentage according to the eligibility criteria. Based on the data analysis, the feasibility validation of the developed media obtained 92% material expert validation, 93% media expert validation, 97% practitioner validation. While the percentage of student response questionnaire results on a small scale is 97% and the percentage of student response questionnaire results on a large scale is 96%. Based on this, it can be concluded that classpoint-based learning media on creative economic materials are suitable for use in the learning process.Keywords: Learning Media, ClassPoint, Creative Economy.